Training specificity of hurdle vs. countermovement jump training - Cappa, D. F.; Behm, D. G. (The Journal of Strength and Conditioning Research, 2011)
The objective of this study was to compare bilateral and unilateral hurdle jumps with traditional countermovement jumps (CMJs). Thirteen athletes were tested during continuous forward bilateral and unilateral hurdle jumps and single CMJ. Countermovement jump height was used to establish the hurdle height. Subjects jumped forward over 4 hurdles with the force plate positioned after the second hurdle to measure vertical ground reaction force (VGRF), contact time (CT), and rate of force development (RFD). For bilateral jumps, hurdle height was established at maximal (100%) CMJ height and at 120, 140, and 160% of the CMJ height. The athletes were instructed to jump as fast as possible to mimic a training session drill. For unilateral jumps, hurdle height was set at 70, 80, and 90% of the CMJ height. Bilateral 160% jumps showed a significantly longer CT than bilateral 100, 120, and 140% jumps. The bilateral 100, 120, and 140% jumps had significantly shorter CT than the unilateral jumps and CMJ. The VGRF during bilateral jumps was higher than unilateral jumps and CMJ. Bilateral 160% jump RFD was significantly higher than CMJ and unilateral jumps but significantly lower than the other bilateral jumps. In conclusion, the characteristics of the bilateral jumps were substantially different from those of the CMJ and unilateral hurdle jumps. As bilateral hurdle jumps with a height between 100 and 140% of the CMJ provide similar CTs and VGRF as many reported sprint or jump actions, they may be considered a more training-specific power training drill than the CMJ.